Neither confirm nor deny : how the Glomar mission shielded the CIA from transparency - Bennett, M. Todd (Columbia University Press, 2023)
"In 1974, a mining vessel, the Hughes Glomar Explorer (ostensibly owned by eccentric billionaire Howard Hughes), descended to the floor of the Pacific Ocean near Hawaii. Its purpose was not, as was publicly recorded, to tap into natural manganese deposits, but rather to recover a sunken Soviet nuclear submarine that had mysteriously disappeared six years earlier. The secrets and intelligence onboard that submarine could, the CIA hoped, win them the underwater Cold War. In Neither Confirm Nor Deny, historian Todd Bennett recounts the logistics, drama, and media fallout of the most daring and expensive Cold War intelligence operation that the CIA carried out. When the Glomar's claw accidentally broke the submarine in half, and when burglars stole documents from the Hughes mansion in Los Angeles and ransomed them to the CIA for $1 million dollars, CIA director William Colby embarked on a media campaign to silence or counter investigative reports that threatened to expose the $350 million boondoggle. What followed would change the relationship between the Fourth Estate and the U.S. intelligence community and disrupt the balance of security and transparency for decades to come, coining in the process what would become known as the Glomar response: "The CIA can neither confirm nor deny....""-- Provided by publisher.
Keywords: United States. -- Central Intelligence Agency -- History -- 20th century.; Glomar Explorer (Ship); United States. -- Central Intelligence Agency; Espionage, American -- Soviet Union -- History -- 20th century.; Intelligence service -- United States -- History -- 20th century.; Cold War.; Espionnage américain -- URSS -- Histoire -- 20e siècle.; Guerre froide.; HISTORY / Military / Intelligence & Espionage.; Espionage, American; Intelligence service; Soviet Union; United States; 1900-1999; History